(untitled) (Educational Dimension, 2025)
Students whose parents are actively involved in their education are more likely to develop a positive attitude toward schooling and to persist in their studies. A significant challenge affecting student retention in schools is the lack of parental involvement in their children’s education. This study explores the relationship between the demographic characteristics of parents and their participation in promoting student retention in secondary schools within Kwimba District. Data were gathered using a questionnaire administered to 126 respondents, selected through simple random sampling. To analyze the data, the Mann-Whitney U Test and Kruskal-Wallis Test were employed to assess the relationships among various demographic factors of the respondents, including gender, age, education level, marital status, and employment status. The results revealed that there was no significant correlation found between home-based parental involvement for student retention in secondary schools and the parent’s age, gender, or marital status. The findings indicate a significant correlation between parents’ work status and their children’s educational attainment. These results underscore the importance of parental involvement in enhancing student retention, highlighting the necessity for targeted interventions to promote such engagement. Increased parental participation, particularly in home-based educational activities, has the potential to substantially decrease dropout rates and improve attendance, ultimately leading to better educational outcomes. The study suggests that parents, regardless of their educational backgrounds or employment statuses, should be encouraged to actively support and motivate their children in academic pursuits to enhance their retention in school.